Konsep Garapan Karya Tari Mahan Mata - Juniarti, Salika (PPSDP Undergraduate Journal of Educational Sciences, 2025)
A dance work creation is definitely the one that mainly finds the concept of work for making a story or background of a dance work. In this writing describes the concept of Mahan Mata dance, Mahan Mata dance is a dance that raises the life story of a mother and her extraordinary children and not a few people feel this story in real life, although as a choreographer this dance work is not directly involved in the incident but can also feel what is felt by the people around them through stories from other people or seeing the incident. In this dance describes their life journey starting from living happily together then in order to fulfill their needs they are willing to live far apart until one day their children feel the loss of the most beloved person, namely their mother, where every living creature will return to the creator. the choreographer has his own reasons for lifting this story into a dance work of art, namely the choreographer's interest in the struggle and love of a mother and her extraordinary children. The purpose of this writing is to describe the concept of Mahan Mata dance work with the method of choreography creation. The creation process starts from determining ideas for creating a dance background, exploration and improvisation, formation to evaluation.